2011
DOI: 10.1186/2045-7022-1-2
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic tools in Rhinology EAACI position paper

Abstract: This EAACI Task Force document aims at providing the readers with a comprehensive and complete overview of the currently available tools for diagnosis of nasal and sino-nasal disease. We have tried to logically order the different important issues related to history taking, clinical examination and additional investigative tools for evaluation of the severity of sinonasal disease into a consensus document. A panel of European experts in the field of Rhinology has contributed to this consensus document on Diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
178
2
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(193 citation statements)
references
References 145 publications
(174 reference statements)
2
178
2
11
Order By: Relevance
“…Two schoolchildren from the control group were unable to adequately coordinate breathing to enable measurement of nasal resistance and had to withdraw from the study. This finding had been reported by others and pointed out as one of the main advantages of AR over AAR [5,8].…”
Section: Resultssupporting
confidence: 49%
See 1 more Smart Citation
“…Two schoolchildren from the control group were unable to adequately coordinate breathing to enable measurement of nasal resistance and had to withdraw from the study. This finding had been reported by others and pointed out as one of the main advantages of AR over AAR [5,8].…”
Section: Resultssupporting
confidence: 49%
“…Unlike other techniques, AR does not depend on patient cooperation and is considered suitable for the study of children [7,8]. Several studies have shown that evaluation of nasal volumes using AR is reliable and reproducible [9].…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of the maximal inspiratory air flow rate can be a convenient method of objective evaluation of the therapeutic response in patients with inferior turbinate hypertrophy [18]. Moreover, nasal inspiration is most strongly correlated with the subjective feeling of nasal obstruction, and NIPF provides a physiological measurement of the air flow through the nose [19]. In the present study, NIPF and nasal obstruction VAS scores were significantly improved in both groups after the treatment.…”
Section: Discussionsupporting
confidence: 51%
“…Los criterios de inclusión fueron los siguientes: historia clínica sugestiva de alergia respiratoria a ácaros de polvo establecida por alergólogos con base en los criterios de la Global Initiative for Asthma (GINA) y de la iniciativa Allergic Rhinitis and its Impact on Asthma (ARIA) (8,17), así como en la prueba de punción positiva frente a ácaros de polvo usando extractos alergénicos estandarizados para aeroalérgenos comunes de acuerdo con la normativa internacional (18), el pico de flujo nasal inspiratorio y el pico de flujo espiratorio (19), también determinados según los parámetros internacionales estandarizados (20). Los criterios de exclusión fueron aquellos propuestos por la World Allergy Organization (WAO) para la inmunoterapia alergénica (21).…”
Section: Población De Estudiounclassified